(untitled) (Progress Annals: Journal of Progressive Research, 2025)
In the competitive landscape of the tourism industry, effective marketing research is crucial for understanding customer preferences, market trends, and competitive dynamics. This article delves into the significance of marketing research for tourism firms, highlighting its role in identifying customer needs, segmenting markets, and enhancing customer satisfaction